Integrating social values with GPS tracks through Denali National Park and Preserve. (June 2023) - Cai, Chang; van Riper, Carena J.; Johnson, Dana; Stewart, William; Raymond, Christopher M.; Andrade, Riley; Goodson, Devin; Keller, Rose
Abstract: This study advanced knowledge of the geospatial relationships between social values elicited during a participatory mapping exercise and on-ground travel patterns understood through Global Positioning System (GPS) tracking of backcountry visitors to a protected area in Alaska. As one of the first studies to combine social values and real-time use of a protected area landscape, we showcase how these combined forms of knowledge can be better understood when compared against biophysical conditions. Contrary to previous research, we observed that perceived social value hotspots, defined by an abundance of point data, did not fully align with use patterns, suggesting that visitors value areas that are not experienced first-hand. Specifically, backcountry travel routes in Denali were less dispersed than areas perceived to be important. Use was mostly concentrated in backcountry units close to the middle sections of the park road while highly valued units coincided with major landmarks, such as the peak of Denali. Travel cost induced by terrain conditions (summarized by elevation, slope and landcover), accessibility (measured by proximity to the park road), and long-view visual resources all contributed to how observed travel behavior deviated from perceived social values. These findings help inform policy and management decisions about outdoor recreation, visitor safety, and visual resource stewardship. Highlights: We compare hikers' travel paths with social values in a national park in Alaska. Spatial analysis reveals travel routes are less dispersed than social values. Risk, accessibility, and long-view visual resources contribute to the mismatch. GPS data on travel behavior help complement the fulfillment of social values. Results have important implications for public land management and future research.